Exploration of Tax Research in The Era of COVID-19 - Soebroto, Bambang; Puspita, Ayu Fury; Damayanti, Made Tara; Lase, Maria Inggried Soinia; Mufid, Muhammad Farras (AIBPM Publisher, 2023)
The prima donna of Indonesia's state revenue has also been affected by the Covid-19 virus. For the sake of Indonesia's economic recovery, the government issued the Minister of Finance Regulation Number PMK-86/PMK.03/2020 concerning Tax Incentives for Taxpayers Affected by the 2019 Corona Virus Disease Pandemic, Law Number 11 of 2020 concerning Job Creation and Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP). The public, especially researchers, needs to understand the mechanism for compiling and developing research related to the latest issues in the field of taxation to produce quality research, which is the goal of implementing community service activities this time. The material to be delivered includes the preparation of research and the development of research issues in the taxation field. The expected benefits of this activity are that participants understand the preparation and research methods and explore research ideas according to the latest issues and phenomena in the field of taxation. The results showed that more than 60% of the participants felt helped by the socialization with this theme.